Rancang Bangun Mesin Pencetak Briket Arang Dual Fungsi Menggunakan Pisau Potong Berbasis Sensor Untuk Mencapai Hasil Pemotongan Yang Presisi - Mohammad Faliq Syahrudin (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Biochar briquettes are an environmentally friendly alternative energy source made from biomass and have the potential to reduce dependence on fossil fuels. However, briquette molding and cutting processes in SMEs are still performed manually, resulting in low efficiency and non-uniform briquette sizes. Therefore, this study aims to design and develop a dual-function charcoal briquette molding machine using a sensor-based cutting blade to produce more precise and uniform cuts. This research used the Research and Development (R&D) method with the 3D development model (Define, Design, Develop, and Disseminate). The research stages included literature study, machine design, manufacturing and assembly, and machine performance testing. Testing was conducted three times using corn cob biomass with sensor distance variations of 45 mm, 75 mm, and 85 mm at a machine speed of 1400 rpm. The testing parameters included cutting results and briquette size uniformity. The results showed that the machine operated properly in both molding and automatic cutting processes. The best performance was obtained at a sensor distance of 45 mm, producing an average of 12.3 proper cuts with a non-conformity level of 0.6 pieces. Meanwhile, sensor distances of 75 mm and 85 mm produced lower cutting precision. These results indicate that the closer the sensor position to the object, the better the detection accuracy and cutting precision, resulting in more uniform briquette sizes. This machine is expected to improve of SME-scale briquette production.